Age-dependent growth responses to climate from trees in Himalayan treeline - Tiwari, Achyut (Nepalese Journal of Zoology, 2020)
Tree rings provide an important biological archive for climate history in relation to the physiological mechanism of tree growth. Higher elevation forests including treelines are reliable indicators of climatic changes, and tree growth at most elevational treelines are sensitive to temperature at moist regions, while it is sensitive to moisture in semi-arid regions. However, there has been very less pieces of evidence regarding the age-related growth sensitivity of high mountain tree species. This study identified the key difference on the growth response of younger (<30 years of age) and older (>30 years) Abeis spectabilis trees from treeline ecotone of the Trans-Himalayan region in central Nepal. The adult trees showed a stronger positive correlation with precipitation (moisture) over juveniles giving the evidence of higher demand of water for adult trees, particularly in early growth seasons (March to May). The relationship between tree ring width indices and mean temperature was also different in juveniles and adult individuals, indicating that the juveniles are more sensitive to temperature whereas the adults are more sensitive to moisture availability. It is emphasized that the age-dependent growth response to climate has to be considered while analyzing the growth-climate relationship of high mountain tree populations.